Enrichment and preservation of a vegetable smoothie with an antioxidant and antimicrobial extract obtained from beet by-products - Fernandez, María Verónica (2020)
This study aims to assess beet leaves extracts (BLE) potential for fruit and vegetable smoothie enrichment and/or preservation. BLE presented a total phenolic content (TPC: 132.43 ± 1.51 g kg−1 dry weight (DW) basis) and an antioxidant capacity (219.2 ± 23.4 mmol kg−1 DW for FRAP and 28.9 ± 0.5 mmol kg−1 DW for DPPH). An antimicrobial activity assay proved BLE effectiveness against Listeria innocua, E. coli and Saccharomyces cerevisiae on systems of pH 3.7 and 7, with initial counts of 4 or 7 log CFU/mL. Incorporation of the BLE into a fruit and vegetable (F&V) smoothie containing orange juice (59%), apples (15%), carrots (15%), BL (6%) and beet stems (5%), significantly increased (50%) TPC of the product as well as their antioxidant capacity. Additionally, extract-enriched smoothies achieved reductions between of 1–3 log cycles in smoothie's native microflora allowing to obtain a one-week shelf-life extension, and presented greater nutritional retention during storage at 5 °C. Therefore, BLE has great potential to be used for the enrichment and preservation of smoothies, bringing great advantages for food industry, consumers and producers.